Whiskey tango foxtrot [videorecording (DVD)] - Fey, Tina, 1970-; Robbie, Margot, 1990-; Freeman, Martin, 1971-; Molina, Alfred, 1953-; Thornton, Billy Bob; Barker, Kim, 1970- (Paramount Home Entertainment, 2016)
Based on journalist Kim Barker's memoir "The Taliban shuffle: strange days in Afghanistan and Pakistan", which details her years as a reporter in Pakistan and Afghanistan beginning in 2002.